If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 2(a + -2) Reorder the terms: 14 = 2(-2 + a) 14 = (-2 * 2 + a * 2) 14 = (-4 + 2a) Solving 14 = -4 + 2a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 14 + -2a = -4 + 2a + -2a Combine like terms: 2a + -2a = 0 14 + -2a = -4 + 0 14 + -2a = -4 Add '-14' to each side of the equation. 14 + -14 + -2a = -4 + -14 Combine like terms: 14 + -14 = 0 0 + -2a = -4 + -14 -2a = -4 + -14 Combine like terms: -4 + -14 = -18 -2a = -18 Divide each side by '-2'. a = 9 Simplifying a = 9
| iz^2-3z-2i=0 | | iz^2+3z-2i=0 | | 3t+3=t+8 | | 14+a=2(a-4) | | 10x^3-7x-3=0 | | kx^2-kx^2=-1 | | X+35=6x | | 4-7a+15-8a-21= | | 1.5x+4=0.25x-3 | | 16h^4-8h^2+1=0 | | 0.875t-2=0.375t+9 | | 2(4x-1)+3x=-13o | | 22.67647059= | | 6=4*-10 | | y=29 | | 5x-4=x+32 | | 5x^4+16x^3+12x^2=0 | | 27a^3+64= | | x^2+3x+88=0 | | x(x+3)=88ft^2 | | 2x-9=57 | | 4(-2c+1)=3c-18 | | 28x^2-x-15=0 | | 12x^3-42x+18=0 | | 4x-9-12-3x=18 | | 14w^2+8w=0 | | 5a+3b+7a-4b= | | 10+4x=7-11x | | 4f^2-15f+14=0 | | 5(x+3)=4 | | 3(5x+2)=6(x+4) | | 3(3x+3)=-7(x+5) |